Translocation of alpha-sarcin across the lipid bilayer of asolectin vesicles. - Oñaderra, M (1993)
alpha-Sarcin is a cytotoxic protein produced by the mould Aspergillus giganteus. Insertion of alpha-sarcin into asolectin membranes has been demonstrated by protein labelling with photoreactive phospholipids. alpha-Sarcin added externally to tRNA-containing asolectin liposomes degrades the entrapped tRNA. Trypsin-containing asolectin liposomes were also prepared. Encapsulated trypsin degrades alpha-sarcin, even in the presence of a large excess of external hen egg-white trypsin inhibitor to prevent any alpha-sarin degradation outside the vesicles. These processes occur only with acidic phospholipids and were not observed when phosphatidylcholine vesicles were used. These results indicate that alpha-sarcin penetrates the lipid bilayer and becomes exposed to the lumen of negatively charged liposomes.